Beyond Borders: Towards a Theology of ‘Synodality’ - Ancheta, Rica Delos Reyes (Archīum Ateneo, 2024)
Pope Francis’ call to pave the way for a synodal Church is revolutionary. While ‘synodality’ has long been a promising Church trajectory, it disrupts and challenges the current status quo in local churches. Moreover, the process of ‘synodality’ is transformative and enriching as it fosters greater engagement of the people at the peripheries of the Church’s life and mission. People in the margins are often perceived as passive participants in the life of the Church and, as it were, on the receiving end. However, the Church’s plans, thrusts, and decisions, whether on a personal level or socio-political and economic affairs, have always involved active and influential parish members and organizations. The ‘influential’ constitutes the majority’s voice in church ministries, activities, and projects. On the other hand, the voices of the underprivileged carry, if any, little weight in the discussion. This paper critically examined avenues for dialogue initiated by the local churches for the synod, allowing the marginalized to sit at the discussion table. It scrutinized a ‘synodal’ Church as it unveiled the mental structures that create categories of marginalization. In the hope of appropriating ‘synodality’ into authentic forms of encounter, solidarity, and dialogue, Koselleck’s ‘space of experience’ and ‘horizon of expectation’ brought into light female narratives in the ‘synodal’ discourse, enabling the process of becoming a ‘synodal’ Church, a desired horizon of the future.